Examining the influence of perceived teaching style on academic burnout - Luky Kurniawan; Ika Tristianti; Natri Sutanti (Psychology, Evaluation, and Technology in Educational Research, 2025)
This research aimed to determine the effect of perceived teaching style on academic burnout in vocational high school students. This research was quantitative research with 50 students who were recruited by a non-probability sampling sample technique. The data were collected using a perceived teaching style questionnaire (Alpha Cronbach=0.817) and an academic burnout instrument (Alpha Cronbach=0.804). The data analysis was simple linear regression. The results of the research showed that the significance value was 0.00 (<0.05), and the t value was 12.971; therefore, it was concluded that the hypothesis was accepted. This also meant that that perceived teaching style had a significant effect on academic burnout at vocational high school. Perceived teaching style consisting of voice intonation, material emphasis, pause timing, eye contact, body movements, and changes in position influenced fatigue, cynicism, and decreased professional efficacy. The R square value of 0.778 shows that perceived teaching style influences 77.8% of academic burnout and the remaining 22.2% are influenced by other factors. Eventually, teachers should have variations in teaching styles such as emphasizing voice to convey important material, providing pause time for students to understand the material, and using body movements. Further research could explore more on how to develop expected teaching style that matched with student needs.